Progress on the nephrite sources of jade artifacts in ancient China from the perspective of isotopes - Wang, Rong; Shi, Xiaowei (Frontiers in Earth Science, 2022)
The use of isotopes is crucial for understanding the origin of nephrite. This article first contrasts recent studies on the radioisotopes and stable isotopes of contemporary nephrite deposits in China, Baikal region, and South Korean Peninsula. It then reviews the isotopic analysis of the sources for discovered nephrite artifacts in China, highlighting the concentration of contemporary nephrite deposits with distinct isotopic fingerprints in three significant geographic areas, Northeast Asia, the Yellow River Basin, and South China Region. In order to support significant archaeological questions regarding the role of jade material utilization in the construction and development of Chinese jade culture and Chinese civilisation, additional isotopic data of jade materials and excavated jadewares must be obtained.